Peningkatan Pemahaman Digital Marketing Melalui Pelatihan di Desa Wisata Gerabah Putaran Miring Melikan Klaten - Anggono, Agus Dwi; Setyowati, Eni; Setyawan, Sidiq; Handayani, Sri (Abdi Geomedisains, 2024)
The digital marketing efforts carried out by the village tourism group partners remain basic and minimal. The product and service photos presented have not yet incorporated appealing and aesthetically pleasing photography elements. This activity aims to improve partners' skills in photography and digital content creation, which are very important in promoting their pottery products in the digital era. The main method of this program is to equip partners with basic photography skills, such as selecting interesting objects, the right shooting angles, and using natural and artificial lighting to produce professional photos. These skills are crucial because the quality of the photos affects the attractiveness of the product in the eyes of consumers. In addition to photography, partners are also guided in creating creative content in the form of videos of the pottery making process, which adds unique value to the product, as well as compiling informative and effective product descriptions. The training was attended by 48 participants, with 96% stating that there was an increase in understanding about digital marketing.